THE LEGAL POWER OF THE AUTHENTICITY OF BIPARTITE JOINT AGREEMENT BETWEEN PT PLATINUM CERAMICS INDUSTRY SURABAYA AND WORKERS - Riawanto, Riawanto; Harianti, Isnin; Rohmah , Mayza H (JILPR Journal Indonesia Law and Policy Review, 2021)
The aim of research is To know the executory power attached to an Act (written proof) and Conducting a legal analysis of a BIPARTITE PB registered with PHI, so that it can be executed appropriately if there is an act of default. The method used is normative juridical law research, which essentially examines laws that are conceptualized as norms or rules that apply in society. The result showed that Notaries play a role in carrying out some of the authority or duties of the state in the civil domain, and are referred to as general officials who are authorized to make AO which is a manifestation of the wilsvorming of the parties, made before a notary or by a notary.